2014
DOI: 10.1002/2014gc005373
|View full text |Cite
|
Sign up to set email alerts
|

Imaging methane hydrates growth dynamics in porous media using synchrotron X‐ray computed microtomography

Abstract: Commercial-scale methane (CH 4 ) extraction from natural hydrate deposits remains a challenge due to, among other factors, a poor understanding of hydrate-host sediment interactions under low-temperature and high-pressure conditions that are conducive to their existence. We report the use of synchrotron X-ray computed microtomography (CMT) to image, for the first time, time-resolved pore-scale methane CH 4 hydrate growth from an aqueous solution containing 5 wt % barium chloride (BaCl 2 ) and pressurized CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 26 publications
(42 reference statements)
2
59
0
Order By: Relevance
“…Whether hydrate can occur as discrete cement or interconnected between pores is still not fully resolved, but recent experiments measuring both hydrate saturation ( S h ) and P ‐wave velocity ( V p ) under pressure are consistent with a load‐bearing hydrate model as presented by Konno et al (). Imaging of methane hydrates using synchrotron X‐ray computed microtomography have also shown methane hydrate to form interconnected networks in porous media (Kerkar et al, ; Sahoo et al, ). In the scenario we postulate, the gas‐hydrate permeability seal was breached as Site U1379 uplifted beyond the upper limit of gas hydrate stability, freeing the methane‐rich fluids to migrate upward and initiate carbonate precipitation at the SMT.…”
Section: Resultsmentioning
confidence: 99%
“…Whether hydrate can occur as discrete cement or interconnected between pores is still not fully resolved, but recent experiments measuring both hydrate saturation ( S h ) and P ‐wave velocity ( V p ) under pressure are consistent with a load‐bearing hydrate model as presented by Konno et al (). Imaging of methane hydrates using synchrotron X‐ray computed microtomography have also shown methane hydrate to form interconnected networks in porous media (Kerkar et al, ; Sahoo et al, ). In the scenario we postulate, the gas‐hydrate permeability seal was breached as Site U1379 uplifted beyond the upper limit of gas hydrate stability, freeing the methane‐rich fluids to migrate upward and initiate carbonate precipitation at the SMT.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the resolution is currently only appropriate for bulk systems, and not for nanopores. Similarly, X‐ray computed synchrotron microtomography can be used to monitor time‐resolved MH growth with a 7.5 μm resolution . This method, for instance, has shown that the hydrate formation starts from dissolved CH 4 rather than from the gas interface.…”
Section: Characterization Of Methane Hydrate In Confined Spacesmentioning
confidence: 99%
“…Moreover, MRI cannot visualize methane hydrate coexist with ice . On the other hand, X‐ray computed tomography (CT) has higher spatial resolution than that of MRI, but it is impossible to distinguish gas hydrate and ice without contrast agents except phase contrast X‐ray CT …”
Section: Characterization Of Methane Hydrate In Confined Spacesmentioning
confidence: 99%
“…The bulk porosity of A‐graded and B‐graded host sands is controlled between 37% and 38%, and the initial water saturation is about 0.5. For reference, various kinds of solutions used as alternatives to pure water can keep enhancing the phase contrast between hydrate and solution in X‐ray CT images during hydrate formation due to the increasing solute concentration (Chen et al, ; Kerkar et al, ; Lei et al, ; Li et al, ; Ta et al, ).…”
Section: Theory and Experimental Methodsmentioning
confidence: 99%